Modernization of Education Governance Based on Accelerative Paradigm Among Pesantren Communities in Madura, Indonesia - Mohammad Thoha; Abd Hannan (Universitas Islam Negeri Mataram, 2022)
This study examines the modernization of education governance through an accelerated learning paradigm among pesantren in Madura. This mixed-method study gathered primary data through interview and observation, while the secondary data were gained from relevant literature sources. This study uncovered two significant findings using education management and social change theories. First, the dynamics of education system governance at several pesantren in Madura have undergone a transformation over the past decade. This transformation is highlighted by the emergence of an accelerated learning system at several pesantrens. Second, implementing an accelerated learning program in the pesantren is conducted by performing modernization on the education governance, entailing two aspects, curriculum and period of study. In the curriculum aspect, accelerated learning and modernization takes shape in the form of learning material implementation based on Takhassus (specialization) program, which uses summaries of several subjects compiled from various book references or sources of the same discipline. In addition, through the takhassus program, each learner can manage and complete their study period in a shorter time.